Nasa-TLX and Sofi Methods as a Tool for Measuring Students' Mental Load and Failure During Online Learning Basic Neurology Physiotherapy Courses - Ida Aryani Pasaribu; Yeni Vera; Sulaiman; Ruri Aditya Sari (Science Midwifery, 2022)
Online lectures are currently being implemented due to the Covid-19 Pandemic. The problem of students who are not accustomed to the demands of independent study due to limited time, facilities, materials and abilities, causes excessive anxiety and panic. This will cause a mental burden that it has an impact on student fatigue which causes a decrease in efficiency, resilience and work capacity. Therefore, this study aims to evaluate the mental workload and fatigue of students during online lectures. Measurement of mental workload using the NASA-TLX method and fatigue measurement using SOFI. The results of this study indicate that the mental workload received by students is in the high category while fatigue is in the medium category. Significant differences in average mental load can be seen based on gender, scientific field, study program accreditation, education level, GPA during online lectures, involvement of student activities, online lecture aids, online lecture venues, how to connect to the network, online tuition fees, and the number of hours of online study. Significant differences in average fatigue can be seen based on gender, study program accreditation, education level, online lecture aids, and the number of hours of online study..